2020
DOI: 10.1111/dth.14317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Gracilaria algae 3% cream vs Clobetasol 0.05% cream in treatment of plaque type psoriasis: A randomized, split‐body, triple‐blinded clinical trial

Abstract: Gracilaria algae is red macro algae which has demonstrated considerable antiinflammatory effects. Our objective was to compare the efficacy of Gracilaria algae topical cream 3% vs Clobetasol cream 0.05% in treatment of plaque-type psoriasis. Thirty adult patients with baseline modified Psoriasis Area and Severity Index (PASI) score ≤12 were randomized to receive either Clobetasol or Gracilaria algae cream on right or left-sided symmetric plaques once daily for 8 weeks and follow-up of 4 weeks. Modified PASI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…With conventional dermatological treatments validated for psoriasis, the use of medicinal plants can be an alternative and auxiliary option. Shatalebi et al 15 studied the Gracilaria algae in comparison with clobetasol, while Yu et al 16 used Paeonia officinalis in combination with acitretin-the outcome in both The sample sizes of the studies included were smaller than those typically found in large intervention trials. However, all of the research outcomes included (improvement in quality of life of psoriasis patients and significant changes in PASI score) were clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…With conventional dermatological treatments validated for psoriasis, the use of medicinal plants can be an alternative and auxiliary option. Shatalebi et al 15 studied the Gracilaria algae in comparison with clobetasol, while Yu et al 16 used Paeonia officinalis in combination with acitretin-the outcome in both The sample sizes of the studies included were smaller than those typically found in large intervention trials. However, all of the research outcomes included (improvement in quality of life of psoriasis patients and significant changes in PASI score) were clinically significant.…”
Section: Discussionmentioning
confidence: 99%